มาตรการทางอาญาในการป้องกันเด็กและเยาวชนจากการถูกล่อลวงในทางเพศโดยอาศัยอินเตอร์เน็ตหรือการสื่อสารทางอิเล็กทรอนิกส์เป็นเครื่องมือ - สุพัตรา สถิตย์จันทรากุล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
At present, children and juvenile sexual grooming through the internet or other electronics communication, internet crime which is violence against children, is worsening and this affects the child who is victimized both bodily and mentally and our society. As for Thailand, applicable provisions have many restrictions which cause enforcement obstacles. Moreover, because of that restrictions caused law enforcement authority have no tools to prevent children and juvenile from sexual abuse either. From the research, the considerable counts which could applied to sexual grooming through the internet or other electronics communication offence are offences of rape and offences of committing indecent act. However, both offences, substantive offence is needed. Consequently, in Thailand enactment of a specific law regulating against sexual grooming through the internet or other electronics communications is needed. Besides, to prevent children and juvenile from being sexual groomed more effective, other measures should be considered as well, such as encouraging international collaboration, or even establishing any authority to control and examine internet usage or electronics communication that would lead to sexual grooming. However, author summarized outcome of law issues as mentioned and also suggested the solution in order to resolve sexual grooming problems in this research